Effects of Motivational Orientation on Learning Drawing in students with Intellectual Disability in Lahore - Hina Noor, Sehrish Riaz, Sadia Batool (JCTE, 2023)
Motivation donates to a person's desire, need, or urge to perform any action. Motivational orientation defines the reasons working behind the motivation to perform that action or achieve the goal. The study was planned to explore the effects of motivational orientation on the learning of drawing in students with intellectual disabilities (ID). A stratified random sampling technique was used to select 200 students with ID (147 male, 53 female) from Lahore Division belonging to the age range 10 to 21 years. The Scale of Intrinsic versus Extrinsic Orientations in the classroom Questionnaire (IEO) developed by Harter (1981) containing 30 items (score 1 describes most extrinsic and score 4 describes most intrinsic) was used to identify the motivational orientation of the students with ID. Beery VMI 6th.ed (Beery, 2010) containing 24 drawing shapes were administered to explore the learning of drawing skills in the students with ID. Both scales were found to be reliable for the given population as the alpha reliability of IEO and Beery VMI were 0.953 and 0.950 respectively. Results obtained by using the statistical techniques of ANOVA, correlation, and regression analysis indicated that ID students with intrinsic motivation have a significant positive relationship with drawing learning whereas extrinsic motivation was found to be negatively correlated with the learning of drawing. It was recommended that intrinsic motivational orientation should be developed in students with ID so that their learning could be enhanced.